A seguran??a do paciente na cultura organizacional: a percep????o das lideran??as de institui????es de diferentes naturezas administrativas - Silva, Natasha Dejigov Monteiro da (2014)
Considering patient safety one of the critical points that reflect the performance of a hospital organization, this study aimed to identify how patient safety is included in the organizational culture of hospital organizations in S??o Paulo, different in their administrative nature: public hospitals of direct administration, public hospitals operated by management contract, and private hospitals. The methodological strategy used was the multiple-case study, applying a self-assessment questionnaire from the Emergency Care Research Institute (ECRI), translated for the Portuguese language. The questionnaire was applied both to leaders who work directly with patient care and administrative leaders that ensure assistance is not prevented or interrupted, and thus indirectly reflect on patient safety. Qualitative and quantitative questions were graded using a Likert scale and consolidated according to seven dimensions, namely: expectations and safety promotion, support and investment from hospital management, security environment, openness to communication and non-punitive response, organizational learning, teamwork, and feedback (information and communication feedback about errors). Data analysis was performed using the statistical programSTATATM 12.1, whose response sample was subjected to linear regression for analysis of variance (ANOVA), having an F test of joint statistical significance as decision rule , in which the p-value is zero. The analysis of mean values of the groups in the studied organizations, as perceived by the respondents, showed a gradation among organizations, with higher values concentrating in private institutions. However, when assessing the specifics among the dimensions of safety culture used for the data analysis, it was found that, as perceived by the participants of the study, the most significant dimensions are Security Environment and Organizational Learning, with an explanatory power of 80%. In addition, also as perceived by the agents, the correlation between the above-mentioned dimensions is stronger in direct administration organizations, followed by the institutions under governmental autonomous administration.